Gravitational dismantling of the Miocene mountain front of the Gibraltar Arc system deduced from the analysis of an olistostromic complex (western Betics) - E. SUADES; A. CRESPO-BLANC (Geologica Acta, 2013)
A mélange complex seals the internal-external zone boundary of the western part of the Gibraltar Arc orogenic belt and constitutes a key element to establish milestones of the Betic-Rif tectonic evolution. The blocks and olistoliths embedded in this mélange provide constraints on the geological history of the main tectonic units involved in the Miocene mountain front. We mapped and analysed the blocks and olistoliths included in this mélange in order to understand its age and genesis, which have long been a matter of debate. The relationships of this mélange La Joya Olistostromic Complex (LaJOC) with the basement units together with the high variability of the block lithologies suggest a sedimentary origin for this mélange. Two large-scale olistoliths retain their original structure prior to their emplacement in the LaJOC Basin. The sedimentological and structural analysis allowed us to correlate these olistoliths with the folded and thrust sequence belonging to the Miocene Betic-Rif accretionary prism (Flysch Trough units), and to constrain the age of deposition of the La Joya Olistostromic Complex. The age of the matrix of the mélange deposits is poorly known because of the lack of in-place fauna. Indeed, the formation of the inherited fold-and-thrust structure of these olistoliths is well-known in the western Betics. Accordingly, the LaJOC should have been deposited during middle Miocene times and the blocks and olistoliths included within the mélange would derive from the gravitational dismantling of the Gibraltar Arc mountain front. The data presented help us to understand the formation of reliefs and basins in the western part of the Gibraltar Arc orogenic system.